We Are Taking In The Fair - F. Gilbert Pollay::::::::: (The 20th Century Music Publishers)
Piano and vocal score, 3 p. At head of title on front cover: A Century of Progress Chicago 1933-34 Worlds fair, On cover is aerial view of the exposition at night. (C-450, c Norton R. Addy), Also on front cover: Fox trot song.